Mucosal Injury During Per-oral Endoscopic Myotomy: A Single-Center Experience - Yeniova, Abdullah Özgür; Yoo, In Kyung; Cho, Joo Young (Turkish Journal of Gastroenterology, 2022)
Background: Peroral endoscopic myotomy is associated with a low risk of adverse events. Mucosal injury is the most common intraprocedural adverse event of peroral endoscopic myotomy. Severe mucosal injury may cause serious consequences, such as esophageal leak and mediastinitis, which affect the outcome of the procedure and prolong hospital stay. The aim of the present study was to determine the characteristics, predictors, and management approaches for unintended mucosal injury during peroral endoscopic myotomy. Methods: A total of 211 patients who underwent peroral endoscopic myotomy between November 2014 and June 2019 were enrolled in this study. Mucosal injury was defined according to a previous study and maintained in the endoscopy database. Patient-related and procedure-related factors were compared between patients with and without mucosal injury. Multivariate analysis was performed after adjusting for confounding factors. Results: A total of 206 patients were eligible for study enrollment. Of these, 44 experienced mucosal injury, with an overall frequency of 21.4% (44/206). On multivariable analysis, mucosal injury was associated with submucosal fibrosis (odds ratio, 8.33; P = .024), intraprocedural bleeding (OR, 14.29; P < .001), endoscopic diameter of 9.9 mm (OR, 4.389; P = .006), and procedure duration over 60 minutes (OR, 1.016; P = .034). Conclusion: Mucosal injury is a significant event encountered during peroral endoscopic myotomy, affecting its short- and long-term outcomes. Intra-procedural bleeding, endoscopic submucosal fibrosis, and use of an endoscope with a large outer diameter have been found to be significant predictors of mucosal injury. Endoscopists should pay more attention to risk factors associated with mucosal injury to avoid adverse events. Cite this article as: Yeniova AÖ, Kyung Yoo I, Young Cho J. Mucosal injury during per-oral endoscopic myotomy: A single-center experience. Turk J Gastroenterol. 2022;33(11):985-994.